Number one Wisma Putra - Fauziah Mohamad Taib (Institute of Diplomacyy and Foreign Relations, Ministry of Roreign Affairs, Malaysia, 2006)
This book, is an extraordinary accomplishment . It contains first-hand recollections by people at No.1, Wisma Putra - the present-day address of the new Ministry of Foreign Affairs in the new administrative capital, Putrajaya.